Scurvy incidence trend among children hospitalised in France, 2015–2023: a population-based interrupted time-series analysisResearch in context - Zein Assad; Maelle Trad; Zaba Valtuille; Cécile Dumaine; Albert Faye; Tania Ikowsky; Florentia Kaguelidou; Lindsay Osei; Naim Ouldali; Ulrich Meinzer (The Lancet Regional Health. Europe)
Summary: Background: Scurvy, historically rare in-high income countries, has re-emerged as an indicator of socioeconomic and dietary disparities. Limited data exist on scurvy trends among European children, particularly following socioeconomic changes since the COVID-19 pandemic. This study analysed scurvy incidence trends among French children over a nine-year period, examining potential post-pandemic increases. Methods: This cohort study used an interrupted time-series analysis of patient records from a national hospital-based French surveillance system. All children aged <18 years hospitalized with scurvy and malnutrition from January 2015 to November 2023 were included. The monthly incidence of hospitalized scurvy per 100,000 children was analysed using a segmented linear regression model with autoregressive error. Incidence of hospitalization for malnutrition was analysed as secondary outcome and for urinary tract infection and vitamin D deficiency as control outcomes. Findings: A total of 888 children were hospitalized with scurvy (median age, 11 years; interquartile range [IQR], 4–15; 431 boys [48.5%]). The COVID-19 pandemic in March 2020 was associated with a significant increase in scurvy incidence (cumulative increase, 34.5%; 95% confidence interval [CI], 12.7–56.3; p = 0.002) and severe malnutrition (cumulative increase, 20.3%; 95% CI, 10.7–29.9; p < 0.001). The increased incidence of scurvy was correlated with the rise in the consumer price index. In contrast, no change was found for the two control outcomes. Interpretation: This study identifies a significant increase in scurvy and severe malnutrition post-COVID-19, associated with inflation and socioeconomic instability, emphasizing the urgent need for targeted nutritional support for at-risk paediatric populations. Funding: None.